Comparative study on histological structure of gill and kidney of snakehead fish (Channa striata, BLOCH 1793) from the Kulim and Sibam Rivers, Riau Province - Sri Wahyuni; Windarti '; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Snakehead fish (Channa striata) is present in the Kulim River that has relatively good water quality, as well as in the Sibam River that has polluted water. The water condition of the rivers my affects the fish health status in general. To understand the histologcal structure of gill and kidney of the fish from those rivers, a study has been conducted from Januari to March 2017. Fish organs were histologically processed and stained (HE). Results shown that in general, the histological structure of gill and kidney of fish from both areas are different. The cell structure of the Sibam’s fish shown abnormality, while those of the Kulim’s fish were normal. Cell abnormality such as hyperplasia and fused lamella in the gill and damaged glomelurus cells and nekrosis are present in the kidneyof the Sibam fish. The histological study shown that the water quality affects the structure of gill and kidney of snakehead fish from the study areas.Key word: Kulim River, Sibam River, Channa striata, Fused lamellae, Gill Structure